2021
DOI: 10.1002/cpp.2684
|View full text |Cite
|
Sign up to set email alerts
|

Information seeking and health anxiety during the COVID‐19 pandemic: The mediating role of catastrophic cognitions

Abstract: Cognitive–behavioural models of health anxiety propose a positive association between information seeking and health anxiety; however, it is unclear the extent to which cognitive mechanisms may mediate this relationship. Catastrophic cognitions are one type of cognition that may mediate this relationship, and the COVID‐19 pandemic has presented an opportunity to examine these relationships within the context of a global health catastrophe. The current study investigated both cross‐sectional ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
0
16
1
1
Order By: Relevance
“…We therefore recommend that efforts aiming at providing information on COVID-19 to people with lower health literacy should concentrate on personal discussion or education about optimal internet navigation and reliable online resources. An association between health anxiety and informationseeking has been often found in previous research, but there is no evidence that the relationship between the two variables is one-directional [34]. The current study did not find any association between frequency of CISB or any group of information sources and worry and anxiety.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…We therefore recommend that efforts aiming at providing information on COVID-19 to people with lower health literacy should concentrate on personal discussion or education about optimal internet navigation and reliable online resources. An association between health anxiety and informationseeking has been often found in previous research, but there is no evidence that the relationship between the two variables is one-directional [34]. The current study did not find any association between frequency of CISB or any group of information sources and worry and anxiety.…”
Section: Discussioncontrasting
confidence: 69%
“…An association between health anxiety and information-seeking has been often found in previous research, but there is no evidence that the relationship between the two variables is one-directional [ 34 ]. The current study did not find any association between frequency of CISB or any group of information sources and worry and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Intolerance of uncertainty includes the belief that uncertain events are unfair, unacceptable and threatening [23]. In such situations, catastrophic cognitions occur, which mediate the relationship between information seeking and health anxiety [24]. It was also found that catastrophic thinking about COVID-19 can contribute to various psychiatric symptoms associated with depression, agoraphobia and panic disorder [25].…”
Section: Discussionmentioning
confidence: 99%
“…Information seeking can also be a reassurance seeking behaviour aimed at reducing health-related fears and is particularly common where there is uncertainty about information presented in the media related to a specific topic ( Guillaume & Bath, 2004 ). However, a high-level of information seeking can be associated with higher health anxiety ( McMullan et al, 2019 ; Jagtap, Shamblaw, Rumas & Best, 2021 ) and it is suggested that it can actually increase anxiety due to negative reinforcement ( Starcevic & Berle, 2013 ). Relatedly, previous research has also shown that media messaging about infectious diseases can increase perceptions of public risk and anxiety ( Sell et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%